PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE, DAN PERSISTENSI LABA TERHADAP KINERJA SAHAM DI PASAR MODAL PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anggraini, Diana Putri; Wijayanti, Anita (E-Jurnal Akuntansi TSM, 2025)
This quantitative study aims to provide empirical evidence on the influence of dividend policy, leverage, and earnings persistence on stock performance in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This study used secondary data from the companies’ annual financial reports. The sample was selected using a purposive sampling technique, resulting in 98 observational data points from companies that met the research criteria. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 25. This study finds that dividend policy and earnings persistence have a negative and significant effect on stock performance, while leverage has no effect. These findings indicate that in relatively stable sectors such as consumer non-cyclicals, investors tend to give more consideration to internal company factors, such as dividend distribution policy and earnings consistency, when assessing stock prospects and performance.